Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1098/rspb.2019.1644
|View full text |Cite
|
Sign up to set email alerts
|

Sperm cryopreservation reduces offspring growth

Abstract: Sperm cryopreservation is routinely used in reproductive medicine, livestock production and wildlife management. Its effect on offspring performance is often assumed to be negligible, but this still remains to be confirmed in well-controlled within-subject experiments. We use a vertebrate model that allows us to experimentally separate parental and environmental effects to test whether sperm cryopreservation influences offspring phenotype under stress and non-stress conditions, and whether such effects are mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 79 publications
3
17
2
Order By: Relevance
“…To some extent, these results with amphibian spermatozoa mirror those found by Nusbaumer and colleagues [ 102 ] in an experiment in which semen from wild-caught brown trout ( Salmo trutta ) was frozen using a method [ 103 ] that produced fertilization rates comparable to those of non-cryopreserved spermatozoa. Cryopreservation did not reduce fertilization rates or affect embryo viability, but did reduce larval growth by about 4%.…”
Section: Impacts Of Gamete Cryopreservation On Offspring Development ...supporting
confidence: 78%
See 1 more Smart Citation
“…To some extent, these results with amphibian spermatozoa mirror those found by Nusbaumer and colleagues [ 102 ] in an experiment in which semen from wild-caught brown trout ( Salmo trutta ) was frozen using a method [ 103 ] that produced fertilization rates comparable to those of non-cryopreserved spermatozoa. Cryopreservation did not reduce fertilization rates or affect embryo viability, but did reduce larval growth by about 4%.…”
Section: Impacts Of Gamete Cryopreservation On Offspring Development ...supporting
confidence: 78%
“…In their 2014 study, Nusbaumer et al [ 102 ] included an interesting extra treatment in their experiment to evaluate the morphology of juvenile brown trout obtained using cryopreserved spermatozoa. Individual embryos derived from the cryopreserved spermatozoa were either exposed to a pathogenic bacterial suspension ( Aeromonas salmonicida ), or only sham exposed as a control treatment.…”
Section: Impacts Of Gamete Cryopreservation On Offspring Development ...mentioning
confidence: 99%
“…It has been demonstrated in rainbow trout that sperm cryopreservation did not affect fertilization rates 28 , and no effects on development and survival during the embryo stage. However, fertilization of eggs using cryopreserved sperm led to significantly reduced larval growth after hatching 24 . This is in contrast to our study, where after using cryopreserved semen for fertilization of eggs it resulted in increased WBW of the larvae compared to larvae obtained with fresh semen at the end of our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is well known that cryopreservation causes both lethal and sublethal damage to sperm (including DNA fragmentation, oxidative stress and reduced mitochondrial function) with functional consequences for sperm and offspring [114]. A recent study in the brown trout Salmo trutta showed that the processes involved in cryopreservation have negative effects on offspring growth even after just one generation [115]. Cryopreservation may also induce epigenetic changes in sperm, with early indications suggesting that patterns of DNA methylation and histone modification are impacted and may be transmitted over several generations [116].…”
Section: Evolutionary Implications Of Assisted Reproductive Technologiesmentioning
confidence: 99%